PERANAN ZAKAT PETANI KELAPA SAWIT DALAM PENINGKATAN EKONOMI MASYARAKAT DI JORONG LANGGAM SAIYO NAGARI KINALI KECAMATAN KINALI - Dewi Manda Angraini; Yossi Eriawati (Universitas Muhammadiyah Prof Dr Hamka, 2022)
The main problem in this study is how the role of oil palm zakat in improving the economy of the community in Jorong Langgam Saiyo Nagari Kinali, Kinali District. This study aims to determine how the role of oil palms zakat in improving the community's economy, how to calculate oil palm zakat, and how to distribute oil palm zakat in Jorong Langgam Saiyo Nagari Kinali, Kinali District. This study uses a field research method (field research) with a qualitative approach. The results showed that oil palm zakat has an important role in improving the economy of the community in Jorong Langgam Saiyo. Keywords: Zakat, Palm Oil, Distribution.